The first version of SCENARIotCHECK: A Checklist for IoT based Scenarios - de Souza, Bruno Pedraça; Motta, Rebeca Campos; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Contemporary Software Systems, such as Ubiquitous Systems, Context-Aware Systems, and Internet of Things (IoT) led to a new technological revolution, with characteristics like autonomy, seamless connectivity and interaction. The engineering of such systems is challenging due to their novelty and a possible lack of software technologies to deal with them. Together with quality assurance for the system, the artifacts for the development itself should also be assured. One way to ensure the quality of the produced artifacts is software inspections. This paper introduces the SCENARIOTCHECK, a checklist-based inspection technique for IoT-based scenarios. A feasibility study indicated its cost-efficiency and effectiveness in detecting defects in the IoT-based scenario.